Report of discussion between officials of the Trades Union Congress and the Labour Party, and representatives of the Socialist Medical Association, held at Transport House, Smith Square, S.W.1 on 11th August 1936, on the subject of medical and ambulance units being sent to Spain
1936-08-12 041-0001-001 292/946/41/1(i)